Polycystic ovarian syndrome (PCOS) : an audit of how many PCOS patients struggle to lose weight with recommended diet management in a Tygerberg Hospital population - Alwakwak, Asma Ahmed E. (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2022.